Antimicrobial activity of Thai medicinal plants against beverage spoilage microorganisms and their potential in retarding Alzheimer’s disease progression - Nanasombat, Suree; Bubpasawan, Thanawan; Tamaput, Nunthaporn; Srimakhan, Yuwapa (Pharmacognosy Communications)
Thai medicinal plants (34 crude methanolic extracts) were tested for their antimicrobial activities, antiacetylcholinesterase and antioxidant activities, total phenolic and flavonoid contents. Acorus calamus, Cassia alata, Crocus sativus, Nymphaea lotus and Phyllanthus emblica extracts showed strong antimicrobial activity against spoilage yeasts, lactic acid bacteria and acetic acid bacteria tested. Most susceptible yeast strains were Rhodotorula glutinis and Schizosaccharomyces pombe. Kaempferia parviflora, Nelumbo nucifera, Rauvolfia serpentina and Centella asiatica extracts exhibited strong acetylcholinesterase inhibitory activity (more than 70 % inhibition). Terminalia chebula, Cinnamomum bejolghota, Uncaria gambir and P. emblica extracts had the strongest antioxidant activity, EC50 of 387.23 – 490.47 µg extract/mg 2, 2-diphenyl-1-picrylhydrazyl (DPPH) by DPPH radical scavenging activity method and reducing capacity of 656.19 – 774.41 mmol Fe(II)/g by ferric reducing antioxidant power (FRAP) method. U. gambir extract had the highest total phenolic and flavonoid contents (771.59 mg gallic acid equivalents (GAE)/g and 2,292.43 mg quercetin equivalents (QE)/g, respectively).
Keywords: anti-acetylcholinesterase activity; antioxidant activity; phenolics; flavonoids; medicinal plants